Analisis Hubungan antara Sikap Kerja terhadap Minat Berwisata dengan Stres Kerja sebagai Variabel Mediasi - Elisabeth Lintong; Daniel Augustinus (Media Wisata, 2022)
Analysis of The Relationship between Work Attitude Towards Interest in Tourism and Work Stress as A Mediation Variable This study aims to determine the relationship between work attitudes and interest in travelling which is mediated by work stress on hotel employees in Medan City, North Sumatra. This study uses quantitative research methods and data collection techniques used are questionnaires and literature study. The results of the study in addition to using a score measurement test. There is or is a relationship between work attitude and travel interest among hotel employees, but the relationship is of little value. Tourist interest in hotel employees may be influenced by other factors. There is no relationship between work stress and interest in travelling, this shows that work stress does not affect hotel employees' travel. There is a relationship between work attitude and work stress, this shows that the work attitude of employees at the hotel where they work has an effect on work stress. The indirect impact of work stress on interest in travelling was found to be insignificant. It turned out that work stress did not mediate the relationship between work attitude and interest in travelling to hotel employees in Medan City.